Preoperative Evaluation with fMRI of Patients with Intracranial Gliomas - Ioannis Z. Kapsalakis; Eftychia Z. Kapsalaki; Efstathios D. Gotsis; Dimitrios Verganelakis; Panagiotis Toulas; Georgios Hadjigeorgiou; Indug Chung; Ioannis Fezoulidis; Alexandros Papadimitriou; Joe Sam Robinson; Gregory P. Lee; Kostas N. Fountas (Radiology Research and Practice)
Introduction. Aggressive surgical resection constitutes the optimal treatment for intracranial gliomas. However, the proximity of a tumor to eloquent areas requires exact knowledge of its anatomic relationships to functional cortex. The purpose of our study was to evaluate fMRI’s accuracy by comparing it to intraoperative cortical stimulation (DCS) mapping. Material and Methods. Eighty-seven patients, with presumed glioma diagnosis, underwent preoperative fMRI and intraoperative DCS for cortical mapping during tumor resection. Findings of fMRI and DCS were considered concordant if the identified cortical centers were less than 5 mm apart. Pre and postoperative Karnofsky Performance Scale and Spitzer scores were recorded. A postoperative MRI was obtained for assessing the extent of resection. Results. The areas of interest were identified by fMRI and DCS in all participants. The concordance between fMRI and DCS was 91.9% regarding sensory-motor cortex, 100% for visual cortex, and 85.4% for language. Data analysis showed that patients with better functional condition demonstrated higher concordance rates, while there also was a weak association between tumor grade and concordance rate. The mean extent of tumor resection was 96.7%. Conclusions. Functional MRI is a highly accurate preoperative methodology for sensory-motor mapping. However, in language mapping, DCS remains necessary for accurate localization.